Citizens' attitudes towards migrant workers in Qatar*. (2nd January 2017) - Diop, Abdoulaye; Le, Kien Trung; Johnston, Trevor; Ewers, Michael
Abstract : Public attitudes play a critical role in shaping policies towards immigration and the status of migrant workers. Facing growing pressure from international human rights organizations, media and other groups, the Gulf Cooperation Council states have begun efforts to reform the current kafala system, which prevails throughout the region. Yet despite these efforts, relatively little is known about what citizens actually think of this policy, let alone their more general attitudes towards foreign workers. In the following paper, we explore this question and focus on the case of Qatar. Recently, the Qatari government promised to reform their sponsorship system in 2015. Whether this reform succeeds will depend on public attitudes towards this new policy and how citizens perceive the role of foreign workers in the country. Drawing on data from a nationally representative survey in Qatar, we use a split sample technique to better disentangle citizens' varying attitudes towards blue-collar and white-collar workers. The survey results suggest that Qatari citizens are ambivalent about foreign workers' contributions and overall impact on their country. While they value foreign workers' positive contribution to the development of their country in general, they have concerns about this population's impact on economic and health resources. Ultimately, most citizens would prefer to maintain the sponsorship system, or kafala, as it is right now.